2013
DOI: 10.1007/s10639-012-9247-3
|View full text |Cite
|
Sign up to set email alerts
|

A competence-based industrial learning approach for factories of the future

Abstract: Manufacturing industry can improve its competitiveness through innovation and technological excellence, and appropriate Industrial Learning can help to achieve this goal through allowing the manufacturing workforce to acquire new skills related to the advanced developments in information and communication technologies. This raises the need for new Industrial Learning tools and methods from the viewpoint of learning content, learning processes, and delivery mechanisms. In this paper, we present a generic compet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…That is, nowadays, companies handle a greater volume of information that is more complex, and, consequently, decision making is more confusing, which implies investing in technology to organize and manage information in a timely and reliable manner. Within the same needs to integrate ICT in production processes, it was found that it directly affects training in ICT, which implies that management must train staff on the use of computer equipment and software and this research has similar conclusions to Kiritsis et al [72], who stated that training in ICT is important for guaranteeing performance. At the same time, it is recommended that when investing in ICT, training in ICT is considered, given that this variable is affected by investment in technology, which means that not only should there be investment in ICT, but also the company must work hard to train the staff to manage, program, and maintain the specialized software, resulting in greater confidence to solve the existing needs of the productive processes.…”
Section: Total Effectssupporting
confidence: 76%
“…That is, nowadays, companies handle a greater volume of information that is more complex, and, consequently, decision making is more confusing, which implies investing in technology to organize and manage information in a timely and reliable manner. Within the same needs to integrate ICT in production processes, it was found that it directly affects training in ICT, which implies that management must train staff on the use of computer equipment and software and this research has similar conclusions to Kiritsis et al [72], who stated that training in ICT is important for guaranteeing performance. At the same time, it is recommended that when investing in ICT, training in ICT is considered, given that this variable is affected by investment in technology, which means that not only should there be investment in ICT, but also the company must work hard to train the staff to manage, program, and maintain the specialized software, resulting in greater confidence to solve the existing needs of the productive processes.…”
Section: Total Effectssupporting
confidence: 76%
“…Especially in high-wage countries, success and output are based on employees’ competences and knowledge (Bullinger, 2012). In each context, knowledge means all of the facts, information, and theories available to the person (Kiritsis et al , 2013). Competences can be described and evaluated both in theory and in practice (Meyer et al , 2014).…”
Section: The Theoretical Frameworkmentioning
confidence: 99%
“…The quantitative evaluation of the training and the skill classification is addressed by the TAM, which partially stems from the work of Kiritsis et al [13], who proposed the ActionPlanT Industrial Learning (IL) methodology for the implementation and evaluation of IL actions specifically addressing the last developments of ICT for manufacturing. It is in this framework that an evaluation approach based on Kirkpatrick's training evaluation model was presented.…”
Section: Training Analytics Model (Tam)mentioning
confidence: 99%